Uji Total Mikroba, Kadar Air, dan pH Ikan Nila (Oreochromis niloticus) Dengan Perendaman Ekstrak Belimbing Wuluh (Averrhoa bilimbi L) Selama Penyimpanan Suhu Ruang - Nurfadilah; Maya Novitasari; Safriyanto Maruka (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2023)
Tilapia fish are susceptible to the process of decay, within 2 hours after death the tilapia fish will experience a decline in physical quality. Starfruit extract contains active compounds, namely saponins, triterpenoids and several minerals which are antibacterial substances. This research aims to determine the effect of starfruit extract on the total microbial test, water content and pH of tilapia during room temperature storage. Data analysis used a Completely Randomized Design (CRD). Data were analyzed descriptively for total microbial testing using the Indonesian National Standard calculation method SNI 2332.3-2015 and SNI 01-2346-2006. The differences in treatment in this study were made by differences in the concentration of starfruit extract. The concentration of starfruit juice given was 0 gr (P1), 40 g (P2), 60 gr (P3), 80 gr (P4) and 100 gr (P5) with four repetitions. The samples were then stored at room temperature for 8 hours. Based on the research results, it can be seen that starfruit extract has an influence on the total microbial value, Based on the research results, it can be seen that starfruit extract has an influence on the total microbial value, pH value and water content value of tilapia fish. The number of bacterial colonies in the treatment with the highest amount of extract (100 grams) with the lowest total microbial value was 2.49 x 105 colonies/g. Also, the pH value and water content of all treatments given starfruit extract were still included in the standards for fresh fish. Keywords: Tilapia, Wuluh Starfruit, Total Microbes